INTEGRASI MEDIA DIGITAL DALAM PEMBELAJARAN: STUDI KASUS DI SMP N 5 KOTA BENGKULU - Martina, Feny; Dwi Puspita, Emelda; Alfaiza, Lolla; Triutami, Eyi; Ansori, Muranda (Jurnal Ilmu Pendidikan Islam, 2025)
The development of digital technology has brought significant changes to the world of education, including the learning process in schools. This research aims to analyze how digital media is integrated in learning at SMP N 5 Bengkulu City. The research method used is qualitative with a case study approach. Data was collected through observation, interviews with teachers and students, and documentation. The research results show that the use of digital media in learning increases students' interest in learning, makes access to learning resources easier, and creates a more interactive learning experience. However, some of the challenges faced include limited infrastructure, lack of training for teachers, and frequent technical obstacles. This study recommends improving technological facilities, training for teaching staff, and strengthening policies in the use of digital media to support more effective learning.